Mean Reverting Behavior of Energy Consumption: Evidence from Selected MENA Countries - Bolat, Suleyman; Belke, Murat; Celik, Necati (International Journal of Energy Economics and Policy, 2013)
<!–[if gte mso 9]> 800x600 <![endif]–> This study examines whether the energy consumption for 15 members of the Middle Eastern & North African (MENA) countries is a stationary process over 1971-2010 period. Annual energy consumption data for Algeria, Bahrain, Egypt, Iran, Israel, Jordan, Lebanon, Libya, Morocco, Qatar, Saudi Arabia, Syria, Tunisia, United Arab Emirates and Turkey, is analyzed using the Lagrange Multiplier (LM) unit root test, in which structural breaks in level and/or trend are endogenously determined. The results of the LM test with two breaks showed that the energy consumption per capita in 8 MENA countries is a stationary process. This study suggests that it is possible to design consistent energy policies based on econometric models and forecasts of energy consumption in those 8 MENA countries. Keywords: Energy Consumption; Unit Root; LM test; MENA JEL Classifications: E21; Q43 <!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin:0cm; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Times New Roman","serif"; –> <!–[endif] –>